Fault control paralleled DC-DC converters and novel common mode current based communication strategy decentralized control paralleled inverters - Cheng, Yeong Jia (2008)
One of the well-known methods to achieve higher reliability is by paralleling two or more units of equipments together. This is because the paralleled system has wide advantages over single unit equipment. Advantages include increase of power capability, high reliability, enhanced availability from the fault tolerance with N+1 modules and ease of maintenance with redundancy implementation. This thesis explores and investigates the paralleling of power supply modules, with the aim to achieve decentralized control scheme that assured reliability, flexibility, reduces power ratings of each module, and to overcome the limitation in centralized control scheme as well as conventional droop method. New approaches are developed and verified experimentally, including novel common mode communication strategy, smooth ride-through during fault, and near equal current sharing. Three DC-DC buck converters with 5Vdc/1A output and three single-phase DC-AC inverters with 110Vrms/550VA 60Hz are constructed to verify the approaches developed in this thesis.